Nilai Waktu Uang - Gad Edison; Lis Sintha Oppusunggu (Syntax Literate, 2023)
The time value of money has a major role in financial management in making long-term decisions. The time value of money is needed by managers as a consideration before investing or determining the source of funds. The concept of the time value of money is a concept where money received today has a greater value than the value received in the future. Money held today has a greater value as a result of investing and earning interest. So the future value of money is equal to the entire population in the tth period, and the past value of money is equal to the entire population in the 0th period, and the interest rate is defined as the development of the population in each period. This statement belongs to a false concept, because money is not a creature that can develop. Similarly, time cannot be valued by money